A mindful inquiry towards transformative curriculum vision for inclusive mathematics education. (2nd January 2018) - Luitel, Bal Chandra
ABSTRACT: Exploring ways to develop a transformative curriculum vision for mathematics education that is inclusive to opposing perspectives and ideologies, this mindful inquiry explores "mindless" views embedded in the mathematics curriculum of Nepal; explores narrowly conceived disempowering assumptions within it; engages in dialectical interactional texturing among perspectives; and eventually emerges with its transformative potentiality. In so doing, this reflection on hegemonic worship of modernity identifies Newtonian reductionism, absolutism, and non-fluidity of language, serving mono-cultural perspectives as restraints underlying inclusive mathematics curriculum. Reflecting on this meaning-making, and in seeking an equilibrium view of reality, the inquiry hopefully offers pluralism, synergy, and montage as imperative in making mathematics education more meaningful.